THERMAL RESPONSE OF STRUCTURE AND HYDROXYL ION OF PHENGITE 2M1: AN IN SITU NEUTRON DIFFRACTION AND FTIR STUDY - Mookherjee M.; Redfern S.A.T.; Zhang M. (My University, 2001)
The thermal dependence of the structure of natural phengite-2M1 with chemical formula situ neutron diffraction. The short-range correlated behaviour of the hydroxyl group was probed by FTIR spectroscopy while the long-range correlated hydroxyl structure was studied by neutron diffraction. Changes in long-range ordering of Si and Al on the tetrahedral sites were not observed from neutron diffraction. Structure refinement of the neutron diffraction data by the Rietveld method suggested that the apparent average hydroxyl bond length decreases on heating. The infrared data show a decrease in the stretching frequency of hydroxyl group, however. Possible explanations for these results are explored. It seems most likely that the apparent shortening of the hydroxyl bond length may be an artefact due to an increase in its vibrational amplitude. The anisotropic vibration of the hydroxyl bond as revealed by the anisotropic displacement parameters of H, increases so much that the average length (shown by the neutron refinement) appears to decrease at high temperatures while the local length of the bond, as indicated by FTIR results, increases.
Keywords: mica; phengite-2M1; hydroxyl; neutron diffraction; FTIR; hydrogen bond